ARTICULAÇÃO E MATERIALIZAÇÃO DA POLÍTICA NACIONAL DE EDUCAÇÃO ESPECIAL NA PERSPECTIVA DA EDUCAÇÃO INCLUSIVA EM UM MUNICÍPIO DO ESPÍRITO SANTO - Rocha, Alessandra Silveira (2022)
The purpose of this study was to analyze how the National Policy of Special Education in the Perspective of Inclusive Education/2008 has been articulated and materialized in the system of education in the district of Vila Velha E/S. It conducts a study involving an intense and powerful scenery in order to understand what has been instituted, as public policies, in the district of Vila Velha in the last decade, taking into consideration that such policy has effects, instead of results and has conducted the educational systems to the promotion of responses to the educational needs of the Special Education Target Students (PAEE), through the access of participation and schooling in regular schools. This investigation runs through the events of the inclusion policy in the period of 2008 and 2020. Its methodology, which has a qualitative nature, had as theoretical-methodological path the cartography assumptions in education and analyzes the local public policies instituted by the district throughout the period marked. The research seeks the support of Boaventura de Sousa Santos (2005, 2007a, 2007b, 2008, 2010a, 2010b, 2020), aiming at understanding the importance of listening, feeling and considering the context of practice as the one that enables the translation of knowledge inside other knowledge, also the support of Jefferson Mainardes and Stephen J. Ball (2006, 2011), who translates the local scenery as the one capable of interpreting, creating and recreating public policies and not only implementing them. For the listening moment, it uses the focal group methodology, adapted to the requirement conditions brought in by the social isolation context. The subjects involved in the research were the education professionals working with PAEE in the Area 5 schools in the district of Vila Velha, among them, Teachers, Educators (Pedagogue) and Principals, as well as the families’ representatives and the Secretariat of Education professionals. As per qualitative approach, this research does not aim at results and nor conclusions of facts, but at the comprehension of those movements that the practice context translates when interpreting federal and state public policies of inclusion. Organized into four axes, the analysis of data was based on the construction of know-how of the practice context and the regulations that focus on consolidating the inclusive processes. It was found that, regarding the students with an indication for special education, the district still experiences tensions related to assessment, followup and planning of the processes for the eligibility and schooling of these students. With respect to the professionals who work with special education, despite the work done by the district to be consolidated, administratively, yet, it presents some offer shortages, which has as impacts, a lot of crossings regarding the school organization and, consequently, the perspective of the inclusive view by everyone in the school community. The district has been doing its own drawing, crossing out the lines of its demarcation, not institutionalizing sufficient local public policies that acknowledge the tensions confronted for the permanence, with quality, of the students in the school. The work conditions added up to the precariousness of the Teachers’ performance that struggle for a strong continuing training, suggests great contributions for future discussions.